The tumor burden score may be a discriminator in microwave ablation versus liver resection for hepatocellular carcinoma within the Milan criteria: a propensity score matching and inverse probability of treatment weighting study - Wei, Zeyuan; Xie, Kailing; Xu, Feng; Dai, Chaoliu (Frontiers in Oncology, 2024)
Purpose This study aims to compare the prognostic outcome of resection (RES) and microwave ablation (MWA) in different tumor burden score (TBS) cohorts. Patients and Methods We retrospectively analyzed 479 patients with primary hepatocellular carcinoma (HCC) who underwent RES (n = 329) or MWA (n = 150) with curative intent at our institution. We assessed their overall survival (OS) and progression-free survival (PFS) using the Kaplan–Meier curve. Propensity score matching (PSM) and inverse probability of treatment weighting (IPTW) were performed to minimize selection and confounding biases. Multivariate Cox regression was used to define the association between surgical modalities and outcomes. Results Following PSM, in the TBS ≤3 cohort, the cumulative 1-, 3-, 5- year OS in the RES and MWA groups were 92.5% vs. 98.8%, 82.7% vs. 90.0%, and 82.7% vs. 83.2% (P = 0.366), respectively. The corresponding PFS rates in the RES and MWA groups were 82.7% vs. 88.0%, 63.6% vs. 68.3% and 55.2% vs. 56.3, respectively (P = 0.218). In the TBS >3 cohort, the cumulative 1-, 3-, 5- year OS between the RES and MWA groups were 92.5% vs. 95.0%, 82.8% vs. 73.2% and 76.3% vs. 55.1%, (P = 0.034), respectively. The corresponding PFS rates in the RES and MWA groups were 78.0% vs. 67.5%, 63.6% vs. 37.5% and 55.2% vs. 37.1%, respectively (P = 0.044). The IPTW analysis showed similar results as shown in PSM analysis. The multivariate Cox regression indicated that the type of surgical modality was not associated with a poorer prognostic outcome in the TBS ≤3 cohort, unlike in the TBS >3 cohort. Conclusion TBS, as a discriminator, might help guide treatment decision-making for HCC within the Milan criteria.